The Great Pumpkin Switch - McDonald, Megan (New York Orchard Books, 1992)
An old man tells his grandchildren how he and a friend accidentally smashed the pumpkin his sister was growing and had to find a replacement.
Keywords: Pumpkin -- Fiction; Brothers and sisters -- Fiction